Imaging localized energy states in silicon-doped InGaN nanowires using 4D electron microscopy - Bose, R; Adhikari, A; Burlakov, V; Liu, G; Haque, M; Priante, D; Hedhili, M; Wehbe, N; Zhao, C; Yang, H; Ng, T; Goriely, A; et al. (American Chemical Society, 2018)
Introducing dopants into InGaN NWs is known to significantly improve their device performances through a variety of mechanisms. However, to further optimize device operation under the influence of large specific surfaces, thorough knowledge of ultrafast dynamical processes at the surface and interface of these NWs is imperative. Here, we describe the development of four-dimensional scanning ultrafast electron microscopy (4D S-UEM) as an extremely surface-sensitive method to directly visualize in space and time the enormous impact of silicon doping on the surface-carrier dynamics of InGaN NWs. Two time regimes of surface dynamics are identified for the first time in a 4D S-UEM experiment: an early time behavior (within 200 ps) associated with the deferred evolution of secondary electrons due to the presence of localized trap states that decrease the electron escape rate and a longer time scale behavior (several ns) marked by accelerated charge carrier recombination. The results are further corroborated by conductivity studies carried out in the dark and under illumination.